Species Composition and Distribution of Benthic Foraminifera at Pandan Beach and Trombol Beach, Sarawak - Nurshuhada, Binti Mohd Aris (Universiti Malaysia Sarawak, (UNIMAS), 2014)
Foraminifera are single-cell protists that can be found abundantly at all marine environment. This group of organism is widely use as biological indicator for the marine environment and also plays important role in marine food web. Foraminifera had been reported as the main diet found in the gut of razor clam (Solen regularis). Pandan beach and Trombol beach were chosen as study sites in order to differentiate the benthic foraminifera community structure between the non-razor clam habitat and razor clam habitat. Samplings were carried out on 16 and 18 January 2014. Sediment samples were taken for benthic foraminifera and sediment particle analyses along line transects placed across the intertidal zone. Simultaneously, the physicochemical parameters of water (salinity and pH) and sediment temperature were recorded. The chamber arrangement and aperture position were used for identifying the species. In this study, a total of 15 species of benthic foraminifera were found, in which 9 species were recorded at Pandan beach and 13 species at Trombol beach. This showed that razor clam habitat has more benthic foraminifera species compared to nonrazor clam habitat. Asterorotalia sp. was the most abundant species present at both study sites, while Textularia sp. was the rare species found in this study. The species diversity at Trombol beach was higher compared to Pandan beach. Pearson correlation analyses also showed that the distribution of benthic foraminifera was significantly influenced by the sediment fractions which are fine sand at Pandan beach and very fine sand at Trombol beach.